Trans historical : gender plurality before the modern - LaFleur, Greta, 1981-; Raskolnikov, Masha, 1972-; Kłosowska, Anna, 1966- (Ithaca, New York : Cornell University Press, 2021)
"Trans Historical illuminates the plurality of trans and gendered experiences that flourished in medieval and early modern Greece, Turkey, Poland, France, Belgium, Italy, Spain, North America, and England; expands our understanding of trans pasts; and documents lives that refused or exceeded categories such as "man" or "woman," before frameworks like "transgender," "binary," and "normal.""--
Introduction. The benefits of being trans historical / Anna Kłosowska, Greta LaFleur, and Masha Raskolnikov -- Mapping the borders of sex / Leah DeVun -- Elenx de Cèspedes : indeterminate genders in the Spanish Inquisition / Igor H. De Souza -- The case of Marin le Marcis / Kathleen Perry Long -- The transgender turn : Eleanor Rykener speaks back / M. W. Bychowski -- Wojciech of Poznań and the trans archive, Poland 1550-1561 / Anna Kłosowska -- Recognizing Wilgefortis / Robert Mills -- Performing and desiring gender variance in the Ottoman Empire / Abdulhamit Arvas -- Without magic or miracle : the romance of silence and the prehistory of genderqueerness / Masha Raskolnikov -- Transgender translation, humanism, and periodization : Vasco da Lucena's Deeds of Alexander the Great / Zrinka Stahuljak -- Visualizing the trans-animal body : the hyena in Medieval bestiaries / Emma Campbell -- Maimed limbs and biosalvation : rehabilitation politics in Piers Plowman / Micah James Goodrich -- Where are all the trans women in Byzantium? / Roland Betancourt -- Performing reparative transgender identities from Stage beauty to The king and the clown / Alexa Alice Joubin -- Laid open : examining genders in early America / Scott Larson -- Epilogue: Against consensus / Greta LaFleur.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 26, 2021).
JSTOR
Keywords: Gender nonconformity -- History -- To 1500.; Gender nonconformity -- History -- 16th century; Gender nonconformity -- History -- 17th century; Gender nonconformity -- History -- 18th century; Transgenrisme -- Histoire -- 16e siècle.; Transgenrisme -- Histoire -- 17e siècle.; Transgenrisme -- Histoire -- 18e siècle.; Medieval; HISTORY; LITERARY CRITICISM; Gender Studies; SOCIAL SCIENCE; Gender nonconformity; Gender minorities; Transgenderism; Medicalization; Medical care; To 1799; medieval transgender, early modern transgender, transgender history, trans people in literature, trans people in history; Electronic books; History